Tuning the coordination sphere of octahedral Dy(iii) complexes with silanolate/stannanolate ligands: synthesis, structures and slow relaxation of the magnetization. Issue 47 (9th November 2021) - Long, Jérôme; Tolpygin, Aleksei O.; Cherkasov, Anton V.; Nelyubina, Yulia V.; Guari, Yannick; Larionova, Joulia; Trifonov, Alexander A.
Abstract : This study reports four SMMs based on silanolate or stannanolate ligands cis -[Dy(OSiPh3 )2 (THF)4 ][BPh4 ]·THF·C6 H6 (1 ), cis -[Dy(OSnPh3 )2 (THF)4 ][BPh4 ]·THF·C6 H6· C6 H14 (2 ), fac -[Dy(OSiPh3 )3 (THF)3 ]·THF (3 ) and fac -[Dy(OSiPh3 )3 (bipy)(THF)]·THF (4 ). Abstract : We report the synthesis, crystal structures and magnetic investigations of four octahedral dysprosium complexes based on silanolate or stannanolate ligands of respective formula cis -[Dy(OSiPh3 )2 (THF)4 ][BPh4 ]·THF·C6 H6 (1 ), cis -[Dy(OSnPh3 )2 (THF)4 ][BPh4 ]·THF·C6 H6 ·C6 H14 (2 ), fac -[Dy(OSiPh3 )3 (THF)3 ]·THF (3 ) and fac -[Dy(OSiPh3 )3 (bipy)(THF)]·THF (4 ) (where THF = tetrahydrofuran, Ph = phenyl, bipy = 2, 2′-bipyridine). Whereas complexes 1–3 exhibit a field-induced slow relaxation of the magnetization, 4 is a zero-field single-molecule magnet, which could be rationalized by the introduction of the bidentate bipy ligand providing a more important linearity of the (Si)O–Dy–O(Si) angle through distortion of the coordination sphere.